Productive performance of bean cultivation in the municipality of Olivedos in Paraíba: trends and indicators (2004-2023) - Abreu, Khyson Gomes; Andrade, Wellerson Leite de; Alves, Lionézia Freire; Araujo Neto, Antenor Pereira de; Barbosa, Maykon Douglas Gomes; Silva, Luis Karlos Pereira da; Arruda, Maria Elizângela de; Muniz, Janaina Iris de Azevedo Silva; Sales, Lindomar Pereira da Silva; Isidro, Renato; Barbosa Júnior, Afonso; Souza, Mairla Maria Alves de; et al. (Brazilian Journal of Production Engineering, 2026)
Cowpeas [Vigna unguiculata (L.) Walp], also known as green beans or macassa beans, are legumes of high socioeconomic importance for northeastern Brazil, where they are widely cultivated in semi-arid areas. The crop is strategically important because it supplies the domestic market, enables exports, and is an essential source of income for family farmers. However, as with other agricultural crops, cowpea production is strongly influenced by adverse factors, notably climate variability and the occurrence of phytopathogenic diseases, which can compromise seed yield and quality. In this context, the present study aims to analyze the productive dynamics of beans in the municipality of Olivedos, Paraíba, from 2004 to 2023, seeking to identify trends, productive indicators, and factors responsible for the observed variations. The results indicate high interannual variability, reflecting both the effects of irregular climatic conditions and the positive impacts of adaptation strategies adopted by local farmers. Considering the importance of beans for the subsistence and income of small producers, it is essential to invest in actions that strengthen this production chain. Among these, the adoption of varieties aimed at reducing production instability and increasing the food and economic security of rural families stands out.